Assessment of Thyroid Function Disorders and C-Peptide, CA 19-9, CA-125 Levels in Patients with Gestational Diabetes Mellitus - Baran, Bernas; Sayin, N. Cenk; Inan, Cihan; Kizilirmak, Gonca Busra; Ates, Sinan; G. Varol, Fusun (Gynecology Obstetrics & Reproductive Medicine, 2025)
OBJECTIVES: We aimed to evaluate thyroid function disorders and determine C-peptide, CA 19-9, and CA-125 levels in pregnant women diagnosed with gestational diabetes mellitus. STUDY DESIGN: Data were collected from 80 women aged 18-45 years who were admitted to the Perinatology outpatient clinic of Trakya University Faculty of Medicine at 24-28 weeks of gestation. Sociodemographic characteristics, general health information, pre-pregnancy weight, and current weight were obtained. All participants underwent a 75 g oral glucose tolerance test. Based on the test results, the participants were divided into two groups: those with (n=40) and without gestational diabetes mellitus (GDM) (n=40). Thyroid function tests were assessed by measuring thyroid-stimulating hormone (TSH), free triiodothyronine (fT3), free thyroxine (fT4), anti-thyroglobulin antibody (TgAb), and thyroid peroxidase antibody (anti-TPO) levels. Additionally, amniotic fluid index, complete blood count parameters, blood C-peptide, CA 19-9, and CA-125 values were evaluated. RESULTS: Fasting blood glucose, 1-hour and 2-hour OGTT values, and HbA1c values were higher in pregnant women with GDM. There was no significant difference in mean amniotic fluid index values or in thyroid function test results between pregnant women with GDM and those without. While CA 19-9 values were higher in the GDM group, there was no significant difference in C-peptide and CA-125 levels. Also, higher mean corpuscular volume (MCV) and erythrocyte distribution width (RDW) values were observed in the GDM group. CONCLUSION: Women with GDM have higher CA 19-9 levels than healthy pregnant women. The clinical significance of this finding should be expressed with long-term follow-up studies.